Women, work, and family : how companies thrive with a 21st-century multicultural workforce - Paludi, Michele Antoinette (Santa Barbara, California : Praeger, an imprint of ABC-CLIO, LLC, 2014)
"A sweeping collection of new essays gathers historical background, theoretical perspectives, and the latest research on integrating work and personal life in a multigenerational workforce"--
16. Promoting Employees' Work-Life Balance: Work, Organizational, and Technological Factors17. Part-Time Employment for Women: Implications for Women and Their Children; 18. Moving Beyond Offering Flexible Work Arrangements; 19. Sandwiched In: Women as Child and Elder Caregivers and Employers' Responses; Index; About the Editor and the Contributors.
Includes bibliographical references and index.
Print version record.
Keywords: Women -- Employment; Work and family; Working mothers; Sex discrimination in employment; Travail et familles; Mères au travail; Discrimination sexuelle dans l'emploi.; POLITICAL SCIENCE -- Public Policy -- Cultural Policy; SOCIAL SCIENCE -- Anthropology -- Cultural; SOCIAL SCIENCE -- Popular Culture; Sex discrimination in employment; Women -- Employment; Work and family; Working mothers; Frau; Familie; Berufstätigkeit; Berufliche Integration; USA